2009
DOI: 10.4049/jimmunol.0900036
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Drives Pathogenic IL-17-Producing CD8+ T Cells

Abstract: IL-17-producing CD8؉ T cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(155 citation statements)
references
References 64 publications
5
148
1
1
Order By: Relevance
“…In fact, our data are consistent with recent findings showing that Th17 cells producing IFN-g are capable of mediating regression of established tumors in some murine models. 44,46,47 Collectively, our data suggest that, in our model, Th17-polarized cells mainly mediated tumor 45 Further studies with a selective depletion of effector cells will help to elucidate the exact role that these cells have in the observed antitumoral effect. In summary, we have shown that hybrids of tumor cells and DCs transduced with CD40L induce systemic antitumor immunity, which, in contrast to untransduced fused cells, can eradicate established tumors.…”
Section: Fusion Cell Vaccine With Cd40l Gene Modification E Alvarez Ementioning
confidence: 61%
“…In fact, our data are consistent with recent findings showing that Th17 cells producing IFN-g are capable of mediating regression of established tumors in some murine models. 44,46,47 Collectively, our data suggest that, in our model, Th17-polarized cells mainly mediated tumor 45 Further studies with a selective depletion of effector cells will help to elucidate the exact role that these cells have in the observed antitumoral effect. In summary, we have shown that hybrids of tumor cells and DCs transduced with CD40L induce systemic antitumor immunity, which, in contrast to untransduced fused cells, can eradicate established tumors.…”
Section: Fusion Cell Vaccine With Cd40l Gene Modification E Alvarez Ementioning
confidence: 61%
“…In humans and mice (human chromosome 6, mouse chromosome 1, respectively), the IL-17F gene is located close to the IL-17A gene, whereas genes for the other members are located on different chromosomes (Iwakura et al, 2011). The IL-17A and F are produced by a class of effectors αβ T cells (Th17 and CD8+ cells), NK cells and neutrophils (Ciric et al, 2009;Michel et al, 2008;Weaver et al, 2007). They induce the expression of numerous inflammatory mediators including IL-8, CXC chemokines, granulocyte-colony stimulating factor and prostaglandin E2 (Ferretti et al, 2003;Jones and Chan, 2002;Ruddy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On binding to the IL23R complex, IL-23 mediates its effects by signaling through the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) and NF-κB pathways (13,14). IL-23 modulates responses in multiple cell populations, including differentiation and maintenance of CD4+ Th17 (6,(15)(16)(17) and CD8+ Tc17 cells (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…On binding to the IL23R complex, IL-23 mediates its effects by signaling through the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) and NF-κB pathways (13,14). IL-23 modulates responses in multiple cell populations, including differentiation and maintenance of CD4+ Th17 (6, 15-17) and CD8+ Tc17 cells (18)(19)(20)(21).We considered that the disease-protective R381Q IL23R may result in a loss of function, leading to decreased IL-23/Th17 pathway cytokine production, or a gain of function, leading to enhanced microbial clearance. We find that CD4+CD45RO+ and CD8+ T cells from healthy R381Q IL23R carriers show decreased IL-23-dependent IL-17 and IL-22 production relative to WT IL23R individuals.…”
mentioning
confidence: 99%